Simultaneous topological Bragg and locally resonant edge modes of shear horizontal guided wave in one-dimensional structure. (19th June 2017) - Huang, Hongbo; Chen, Jiujiu; Huo, Shaoyong
Abstract: In this paper, we realize the topological edge modes of a shear horizontal (SH) guided wave in the one-dimensional (1D) composite structure that exist at the phononic band gaps opened at the center of the Brillouin zone (BZ), or at the zone boundary, or both. Furthermore, we investigate the topological edge modes in periodic acoustic systems result from both Bragg scattering and local resonances. In particular, we find and demonstrate that, in our system where topological and trivial defect states coexist, these results provide a new paradigm for manipulating the existence of the interface states in a set of prescribed band gaps that can have potential applications in the design of novel acoustic devices.